2008
DOI: 10.1053/j.gastro.2007.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern, Regulation, and Functions of Methionine Adenosyltransferase 2β Splicing Variants in Hepatoma Cells

Abstract: Background & Aims-Methionine adenosyltransferase (MAT) catalyzes S-adenosylmethionine biosynthesis. Two genes (MAT1A and MAT2A) encode for the catalytic subunit of MAT, while a third gene (MAT2β) encodes for a regulatory subunit that modulates the activity of MAT2A-encoded isoenzyme. We uncovered multiple splicing variants while characterizing its 5′-flanking region. The aims of our current study are to examine the expression pattern, regulation, and functions of the 2 major variants: V1 and V2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 24 publications
1
107
0
Order By: Relevance
“…The magnitude of increase in MAT2␤ protein level is ϳ150-fold in V1-or V2-overexpressing HuH-7 cells, because the baseline expression is absent. Likewise, MAT2␤ is not expressed in normal liver (2,4), and the level of MAT2␤ protein in HCC specimens is comparable to HuH-7 cells overexpressing V1 or V2. There is a faint MAT2␤ band seen in NL1, which may be due to the fact that MAT2␤ is induced in cirrhosis, which is almost always present in the setting of HCC (2).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The magnitude of increase in MAT2␤ protein level is ϳ150-fold in V1-or V2-overexpressing HuH-7 cells, because the baseline expression is absent. Likewise, MAT2␤ is not expressed in normal liver (2,4), and the level of MAT2␤ protein in HCC specimens is comparable to HuH-7 cells overexpressing V1 or V2. There is a faint MAT2␤ band seen in NL1, which may be due to the fact that MAT2␤ is induced in cirrhosis, which is almost always present in the setting of HCC (2).…”
Section: Resultsmentioning
confidence: 94%
“…V1 exerts a stronger effect than V2 on cyclin expression and growth and may be related to the fact that it also exerts a stronger effect in modulating cytoplasmic HuR content. Interestingly, although both variants increase growth, only V1 regulates apoptosis and c-Jun N-terminal kinase signaling (4). There are also differences in the tissue distribution of these two variants, with some tissues expressing predominantly V1, whereas others express V2 (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MATα and MATβ subunits can form several MATαβ complexes (3,4). There are two major splicing forms of the MAT2B gene that encode for MATβV1 and MATβV2, which share very high sequence similarity and differ by only 20 residues in the N terminus (5). We recently reported that MATβ isoforms interact through their C terminus with MATα2 to form the MATαβ complexes MATαβV1 and MATαβV2 (4).…”
mentioning
confidence: 99%